Planning for service management within a service-oriented computing infrastructure a necessary infrastructure for mission critical deployment. - Jones, Bill (SOA webservices journal.)
The more widely service oriented architectures become incorporated into core business applications and processes, the more critical the ability to easily configure, manage and monitor the overall infrastructure becomes.